SUMBER STRES KERJA DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI - Nur Azizah (MediaTrend, 2007)
Work stress is one of important problems in the human resources maintenance, because the work stress able to improve work performance or inhibit the high work achievement. Various conditions can cause the stress in the work place and it can influence the employee performance. This research aimed at, first knowing the work stress sources and employee performance. Second, knowing the  influence of individual stressor variable, group stressor variable, organization stressor variable, and individual difference stressor  as the work stress sources either simultaneously or partially toward employee performance of Communication and Tourism Agency of Malang Regency. Third, knowing the dominant variable toward employee performance. It is explanatory research, that involved 50 respondents as the samples from 100 employees that is registered as the Civil Public Servant at the Agency. The results showed that individual stressor variable, group stressor variable, organization stressor variable, and individual difference variable either   simultaneously  toward the employee of Communication and Tourism Agency of Malang Regency. Then through partial regression, it can be known that the individual stressor, group stressor, organization stressor, and individual difference stressor partially influence significantly toward employee performance. Based on the results, it can be known that  individual stressor variable is the dominant variable that influences employee performance at the Communication and Tourism Agency of Malang Regency